A Two-Stage High-Gain Quadratic Boost Converter Using Inverse-Coupled-Inductors for Low Input-Current Ripple - Alwy Muhammad Ravi; Herlambang Setiadi; Muhammad Zakiyullah Romdlony (LPPM Universitas Negeri Semarang, 2026)
High step-up DC–DC converters are required to interface low-voltage renewable energy sources with higher-voltage dc buses in dc microgrid applications. This paper presents a simulation-based two-stage high-gain DC–DC converter integrating an inverse-coupled-inductor front end with a quadratic boost rear stage. The inverse-coupled front end is employed to reduce source-side input-current ripple and mitigate dc-flux accumulation, thereby lowering the risk of magnetic-core saturation in the front-stage inductors under high-power operation. Compared with uncoupled and direct-coupled configurations, the inverse-coupled arrangement enables ripple-current cancellation between the two input phases, which improves its feasibility for higher-power implementation. The quadratic boost rear stage provides high voltage gain and supports a more stable dc-bus voltage response. Analytical derivations of the operating principle, voltage gain, and input-current ripple ratio are presented, followed by comparative simulation of the three inductor configurations. The results show that the inverse-coupled configuration achieves the lowest average input-current ripple ratio of , with a minimum value of at = 0,5. The converter also produces an output voltage close to 400 V from a 20 V input, corresponding to a voltage gain of approximately 20. These results indicate that the proposed topology offers a promising trade-off between high voltage gain, reduced front-stage magnetic stress, source-side ripple suppression, and output-voltage stability for renewable-energy-fed dc-bus applications.